Faktor yang Berhubungan dengan Pola Asuh Orang Tua Balita ISPA Studi di Puskesmas Cerme Kabupaten Gresik - Rahayu, Silachu Rodjaa Rosyada (Jurnal Riset Kesehatan Masyarakat, 2025)
Background : In Gresik Regency, ARI ranks 4th as the disease with the highest number of cases. The prevalence of ARI cases in toddlers in 2024 is 40.45%. The results of a preliminary study found that the parenting pattern of parents is the most common cause of ARI cases in toddlers at Cerme Health Center. The aim of this study is to determine the factors associated with the parenting patterns of parents of toddlers with ARI in the working area of Cerme Health Center, Gresik Regency. Method: This research uses a quantitative method with an analytical observational study with a cross-sectional design. The total sample in this study is 183 samples taken from the total population of parents of toddlers with ARI who brought their toddlers to Cerme Health Center in March 2025. Data were collected using interviews with a questionnaire that had been tested for validity and reliability. Data analysis used the non-parametric chi-square test to examine the relationship between variables. Result: The results of this study indicate that several factors related to the parenting patterns of parents of toddlers with ARI are employment status, parents' level of knowledge, perceptions of vulnerability and seriousness, and attitudes with the same p-value of 0.000 (p-value < 0.05).  Conclusion: In this study, it was found that the factors related to the parenting patterns of parents of toddlers with ARI are the employment status of parents, level of knowledge, perceptions of disease vulnerability and seriousness, and parents' attitudes.